2009
DOI: 10.1111/j.1463-1326.2008.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced adiposity alters the serum profile of inflammation in C57BL/6N mice as measured by antibody array

Abstract: Morbid obesity is considered a systemic inflammatory state. The objective of this project was to characterize the adipokine, cytokine and chemokine protein profile in serum from control, lean and obese mice. We hypothesized that chemokines and cytokines are altered by caloric restriction and diet-induced obesity as a function of changes in body composition. Six-week-old female C57BL/6N mice (n = 12 per group) were randomized to one of three diets: control (fed ad libitum); lean (30% calorie-restricted regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 39 publications
8
68
3
Order By: Relevance
“…Immune response alterations and carcinogenesis ILP molecules have been reported to play a crucial role in altered inflammatory responses to infectious challenge commonly observed in insulin resistance-related metabolic disorders (Fenton et al 2009, Bitar & Al-Mulla 2012.…”
Section: Insulin Resistance Immune Response Alterations and Cancer:mentioning
confidence: 99%
“…Immune response alterations and carcinogenesis ILP molecules have been reported to play a crucial role in altered inflammatory responses to infectious challenge commonly observed in insulin resistance-related metabolic disorders (Fenton et al 2009, Bitar & Al-Mulla 2012.…”
Section: Insulin Resistance Immune Response Alterations and Cancer:mentioning
confidence: 99%
“…5,6 Similar to obese men, obese mice fed a high fat diet also results in increased adiposity, circulating growth factors and inflammation when compared with control mice and may contribute to prostate cancer progression. [7][8][9][10] Studies suggest that cancer cells undergo an epithelialmesenchymal-transition (EMT) program at the initiation of invasion, which is a critical process for metastasis. 11,12 Hallmarks of EMT include loss or decreased protein expression of e-cadherin, increased vimentin and deregulation of b-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Th1 immune responses are also related to food intake. Furthermore, Fenton et al (2009) reported that Il12 concentration is closely associated with nutritional status in C57BL/6N mice. Reiss et al (1996) also showed that Il12 up-regulates the production of NO in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 12 (Il12)-mediated functions are impaired in Stat4 KO mice Thierfelder et al, 1996). Il12 concentration in blood significantly increases in 30% calorie-restricted animal relative to control (Fenton et al, 2009). It is also known that Il12 activates macrophages and up-regulates nitric oxide (NO) production in response to infection (Reiss et al, 1996).…”
Section: Introductionmentioning
confidence: 99%